Does farmland conversion improve or impair household livelihood in smallholder agriculture system? A case study of Grain for Green project impacts in China's Loess Plateau. (June 2016) - Li, Qirui; Liu, Zhen; Zander, Peter; Hermanns, Till; Wang, Jijun
Highlights: Smallholder agriculture contributes to the rural economy of China, and the Grain for Green project (GGP) is a land retirement policy making land use change in smallholder agricultural systems (SASs). This study aims to find the effect of GGP on the transformation of SAS and household livelihood in Ansai County, China's Loess Plateau. Using survey data collected in 2010, a structural equation model (SEM) was developed to confirm that the GGP intervention of converting farmland and paying compensation did give opportunities to improve land use patterns and household livelihood but also provoked the loss of land and labor in the SAS. Abstract: Smallholder agriculture contributes to the rural economy of China's Loess Plateau, and the Grain for Green project (GGP) is a land retirement policy causing land use change in smallholder agricultural systems (SASs). The article attempts to identify whether the GGP have positive or negative impacts on SAS in Ansai County, China's Loess Plateau. Using official statistics from 1998 to 2009, we first revealed a SAS transformation toward specialized grain and potato production, intensive horticulture and orchards after 1998. Using survey data collected in 2010, a structural equation model (SEM) was developed to confirm the causal effects of the GGP on SAS in 2009 (the 3rd year after farmland retirement). Results showed that the GGP promoted the transformation of SAS and the improvement of household livelihood. Moreover, the GGP intervention of converting farmland and paying compensation gave opportunities to improve land use patterns and household livelihood but also provoked the loss of farmland and labor in SAS. For the sustainability of SAS in long term, commercial agriculture and farmers' engagement and related skills might be enhanced along with continuing the prohibition of annual cropping and grazing on converted land.